Application of the Caprini Risk Assessment Model in Evaluation of Non–Venous Thromboembolism Complications in Plastic and Reconstructive Surgery Patients. (January 2014) - Jeong, Haneol S.; Miller, Travis J.; Davis, Kathryn; Matthew, Anoop; Lysikowski, Jerzy; Lazcano, Eric; Reed, Gary; Kenkel, Jeffrey M.
Background: The Caprini Risk Assessment Model is used to categorize patient risk for venous thromboembolism (VTE) events; its predictive associations have been repeatedly corroborated. Calculating scores involves consideration of systemic factors that may predict other postoperative complications. Objective: This study investigates whether Caprini scores can be applied to non-VTE complications. Methods: The authors undertook a retrospective chart review of 1598 encounters for a series of complex reconstructive and body contouring operations at an academic medical institution. Input variables included Caprini score components, patient comorbidities, and prophylactic use of antithrombotic drugs. Output variables were postoperative complications. Tests for proportions were performed on percentile data. Nonpercentile data were treated with comparison of means ( t test). Odds ratios for complications were calculated for stratified risk groups and compared. Results: The overall complication rate was 28.03%. Deep vein thrombosis (DVT) incidence was 1.50%. Differences in age, body mass index (BMI), operation time, hypertension, diabetes, renal disease, and cancer were statistically significant between patients who experienced complications and those who did not. For DVT versus DVT-free patients, differences in sex, BMI, operation time, smoking status, diabetes, hypertension, and prior DVT were significant. Caprini scores identified 628 encounters as low risk (0-4) and 970 as high risk (>5). Dehiscence, infection, necrosis, seroma, hematoma, and overall complication rate significantly increased the incidence for the high-risk group. Conclusions: Caprini scores can be used as valuable predictors for some non-VTE postoperative complications (dehiscence, infection, seroma, hematoma, and necrosis). In addition to VTE events, clinicians should pay special attention to clinical signs indicative of the complications listed above when dealing with high-risk, high–Caprini score patients. Level of Evidence: 4